Intracranial medulloblastoma as the cause of progressive ataxia in a 6‐month‐old draft horse cross gelding. (25th November 2022) - Palmisano, Megan; Bender, Susan; Johnson, Amy L.
Abstract: We describe the unique clinical presentation of a central nervous system neoplasm in a 6‐month‐old draft horse cross gelding. Based on the neurologic examination at admission, neurolocalization was most consistent with a mildly asymmetric cervical, multifocal, or diffuse myelopathy. Mild vestibular involvement also was considered, but no cranial nerve deficits were observed. The gelding was negative for Sarcocystis neurona or Neospora hughesi based on paired serum and cerebrospinal fluid (CSF) samples analyzed, with no evidence of cervical compression based on contrast myelography. The horse was euthanized because of progression of clinical signs. At necropsy, a mass was identified associated with the cerebellum, and histopathology was consistent with medulloblastoma, which has not been reported previously in the horse.